2021
DOI: 10.1186/s40814-021-00777-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol strength on alcohol consumption: findings from a randomised controlled cross-over pilot trial

Abstract: Background Reducing the alcohol content of drinks has the potential to reduce alcohol consumption. The aims of this study are to (1) test the feasibility of a randomised controlled trial (RCT) to assess the effect of alcohol strength on alcohol consumption within licensed premises in the United Kingdom (UK), and to (2) provide data to estimate key parameters for a RCT. Methods This study is a double-blind randomised controlled cross-over pilot tria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a recently published overview of the literature on production, consumption and impact of low and no‐alcohol drinks [ 5 ], we found very little research on this topic coming from a public health perspective (e.g. on labelling [ 6 , 7 , 8 ] and marketing [ 9 ]) and almost no research focusing on whether low‐ and no‐alcohol products can contribute to reduction in overall ethanol consumption, although at least one innovative trial attempting to answer this question with reduced alcohol beer is currently in progress [ 10 ], and another small study found that reduction in wine alcohol content did not lead to increase of wine consumed [ 11 ]. Thus at this point, it is too early to make conclusions about this approach as a public health measure aimed at reducing alcohol‐related harm.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published overview of the literature on production, consumption and impact of low and no‐alcohol drinks [ 5 ], we found very little research on this topic coming from a public health perspective (e.g. on labelling [ 6 , 7 , 8 ] and marketing [ 9 ]) and almost no research focusing on whether low‐ and no‐alcohol products can contribute to reduction in overall ethanol consumption, although at least one innovative trial attempting to answer this question with reduced alcohol beer is currently in progress [ 10 ], and another small study found that reduction in wine alcohol content did not lead to increase of wine consumed [ 11 ]. Thus at this point, it is too early to make conclusions about this approach as a public health measure aimed at reducing alcohol‐related harm.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a 2009 US study estimated that 26% of alcoholic drink energy content is derived from non‐alcohol ingredients 110 which would allow for further reformulation. Short‐term randomized control trials show that reductions to alcoholic drink serving size 111 and ABV 112 decrease amount of alcohol consumed. Therefore, reformulation could be of particular benefit to consumers as it would result in the amount of energy being consumed from alcoholic drinks decreasing without the need for conscious behavior change.…”
Section: The Impact Of Mandatory Energy Labelling On the Alcohol Indu...mentioning
confidence: 99%
“…The characteristics of alcoholic drinks such as serving size (total volume in a single drink), packaging size (total volume in a full alcohol container), and strength (alcohol by volume [ABV]) affect how much people drink. People consume less alcohol if they drink from smaller serving sizes (Kersbergen et al, 2018; Stevely et al, 2021), smaller wine bottles (Codling et al, 2020), and lower strength products (Perman-Howe et al, 2021). Therefore, changing these product characteristics could improve public health.…”
mentioning
confidence: 99%